2021
DOI: 10.1002/mds.28649
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Abnormalities of the Dentatorubrothalamic Tract in Cervical Dystonia

Abstract: Background The dentatorubrothalamic tract (DRTT) remains understudied in idiopathic cervical dystonia (CD), despite evidence that the pathway is relevant in the pathophysiology of the disorder. Objective The aim of this study was to examine the DRTT in patients with CD using diffusion tensor imaging (DTI)–based tractography. Methods Magnetic resonance imaging scans from 67 participants were collected to calculate diffusion tractography metrics using a binary tractography‐based DRTT template. Fractional anisotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 46 publications
3
27
0
Order By: Relevance
“…12,13 Last, we found no significant correlation between FC maps and clinical scores. This finding is consistent with previous studies on focal dystonia that did not disclose significant correlations between clinical features and imaging parameters 37 and may occur when tests are partly self-administered.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…12,13 Last, we found no significant correlation between FC maps and clinical scores. This finding is consistent with previous studies on focal dystonia that did not disclose significant correlations between clinical features and imaging parameters 37 and may occur when tests are partly self-administered.…”
Section: Discussionsupporting
confidence: 93%
“…Consistently, FC normalization of the thalamus and putamen with the sensorimotor cortex after botulinum toxin treatment was reported by Brodoehl et al 4 Dentate FC alterations in CD may also represent a functional correlate of microstructural changes characterized by decreased axonal integrity in the dentato-rubro-thalamic tract, which is known to be an important relay between sensorimotor network areas. 37 We may speculate that increased FC between the dentate nucleus and thalamus is a mechanism to compensate for structural degeneration. In line with recent literature, 37 our results support evidence of cerebellar outflow pathway alterations in CD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Two very recent cases describe similar improvement in tonic components of craniocervical dystonia after bilateral Vim DBS [33,34]. It is thus possible that in some patients with dystonia, the underlying "circuitopathy" is localized to the cerebellothalamic pathways, as has been suggested by functional and structural neuroimaging [35][36][37]. In these patients, a shared cerebellar pathophysiology may produce both dystonia and an ET-like upper limb postural and action tremor, which would then both respond to DBS of the cerebello-thalamic relay in the Vim.…”
Section: Discussionmentioning
confidence: 88%
“…Of the studies identified, the number of diffusion directions ranged from 6 ( n = 5) [9–13] to ≥60 ( n = 18) [14, 31, 33, 35, 37, 39, 42–45, 49–51, 54, 57–59, 63], the remaining studies using an intermediate number of directions ( n = 10) [30, 32, 34, 36, 38, 40, 41, 46, 52, 53, 55, 56, 60–62, 64–68, 70] or no details were provided ( n = 1) [15]. The b values employed were in typical ranges of 700–1000 s/mm 2 , with five higher at 1100–1500 s/mm 2 [38, 39, 49–51].…”
Section: Resultsmentioning
confidence: 99%